Relasi Teks dan Konteks: Pola Interaksi Al-Qur'an dengan Tradisi Masyarakat dalam Bingkai Living Qur'an - Syahruddin, Siti Masyita; Yusuf, Muhammad; Mahfudz, Muhsin (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
This article examines the pattern of interaction between the Qur’an and societal traditions within the framework of the Living Qur’an. The study is based on the reality that the Qur’an is not merely a normative text but one that is enlivened through the traditions and social expressions of moslems. The purpose of this research is to conceptually explore three patterns of interaction between the Qur’an and tradition, taṣdīq (affirmation), tagyīr (modification), and takwīn (formation of new traditions) as well as to understand the relationship between text and context. The method employed is a literature review with a descriptive-qualitative and socio-historical approach. The findings reveal that taṣdīq reinforces traditions aligned with Islamic values, tagyīr modifies traditions that remain mixed with non-religious elements, and takwīn creates new traditions inspired by Qur’anic values. The Living Qur’an illustrates that the Qur’an is note only understood textually but also actualized through social dan cultural practices. The dialectic between revelation and context generates a complementary moral authority that sustains universal values and religious praxis. This study is expected to provide theoretical contributions to Living Qur’an studies and open further avenues for exploration of this discourse.